Response of methane emission and growth performance of yearling male boer goats to an inclusion of Acacia karroo (sweet thorn) in Avena sativa (common oat) hay based diet - Mathobela, R. M.; Ng’ambi, J. W.; Brown, D.; Chitura, T. (APPLIED ECOLOGY AND ENVIRONMENTAL RESEARCH, 2021)
This study determined the response of methane emission and growth performance of yearling male Boer goats fed a basal diet of Avena sativa hay supplemented with Acacia karroo (sweet thorn) leaf meal. Twelve yearling male Boer goats with initial mean live weights of 23 ± 2 kg were used in a 21-day experiment. The goats were randomly assigned to four dietary treatments, each containing sweet thorn leaf meal at 10, 15, 20 and 30% with Avena sativa hay as a basal diet. The data collected was subjected to analysis of covariance and analysis of variance in a completely randomized design using Statistical Analysis Software. Differences were separated at 5% level of probability. Sweet thorn leaf meal inclusion level had no effect (p > 0.05) on diet intake, methane emission, live weight changes and digestibility. Feed conversion ratio improved linearly with increased Sweet thorn leaf meal inclusion level. The low tannin contents in sweet thorn leaves indicate that these leaves can be safe to use as a source of protein in animal nutrition if used sparingly. Although, sweet thorn leaf meal reduced methane emission, the optimal dose was not determined. Further validation is required to determine sweet thorn inclusion levels for optimal methane production and emission by goats
Journal article published in APPLIED ECOLOGY AND ENVIRONMENTAL RESEARCH 20(2): 1139-1151.
Keywords: Optimal dose; Live weight; Leaves; Tannins; Feed conversion ratio; Tannins; Oats; Hay as feed; Goats -- Feeding and feeds